"In the Grip of King Kong": Making Sense of Whistleblower Retaliation Experiences Through Metaphor - McGlynn, Joseph (Journal of business ethics, 2025)
Whistleblowers frequently endure retaliation from organizations for exposing wrongdoing, but struggle to effectively communicate their experiences of ostracism, exile, and physical intimidation. This qualitative study used a metaphor framework to examine whistleblower experiences of retaliation. Semi-structured interviews were conducted with whistleblowers (N = 21), each of whom had experienced organizational retaliation. Guided by sensemaking theory and reflexive thematic analysis, themes were generated to categorize the metaphors that whistleblowers used to make sense of their experiences, and to portray participant experiences of organizational retaliation through the metaphors identified. Whistleblowers described two primary types of metaphors to describe their experiences of organizational retaliation, including metaphors of violence and metaphors of isolation. Metaphors of violence included metaphors comparing whistleblower experiences to forms of physical harm and mental harm. Metaphors of isolation described whistleblower experiences of professional isolation and relational solitude. The findings of this study inform whistleblowing research by increasing understanding of whistleblower experiences of organizational retaliation, extending knowledge of the types of support needed throughout the whistleblowing process, and providing empirically grounded recommendations to assist past, present, and future whistleblowers in their efforts to fight organizational corruption.